2016
DOI: 10.1007/s00203-016-1248-y
|View full text |Cite
|
Sign up to set email alerts
|

Truncated type IV pilin PilA108 activates the intramembrane protease AlgW to cleave MucA and PilA108 itself in vitro

Abstract: polypeptide with the C-terminal motif WVF, could induce mucoid conversion in the PAO1 strain. In all, our results provided a model of activation of AlgW by another protein ending with proper motifs. Our data suggest that in addition to MucA cleavage, AlgW may cleave other substrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…In addition, inactivation of rpoN1 resulted in the downregulation of type IV prepilin gene tapA in the RN12T4 mutant compared to the wild-type strain (Fig. 6A, B, and C), which may partly account for the decrease of swarming motility in this mutant (24)(25)(26)(27). Furthermore, the transcriptional start site mapping of tapA was determined by primer extension analysis and revealed that the conserved Ϫ24/Ϫ12 motifs (GG and GC) characteristic of 54 -dependent promoters were present upstream of the open reading frame (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…In addition, inactivation of rpoN1 resulted in the downregulation of type IV prepilin gene tapA in the RN12T4 mutant compared to the wild-type strain (Fig. 6A, B, and C), which may partly account for the decrease of swarming motility in this mutant (24)(25)(26)(27). Furthermore, the transcriptional start site mapping of tapA was determined by primer extension analysis and revealed that the conserved Ϫ24/Ϫ12 motifs (GG and GC) characteristic of 54 -dependent promoters were present upstream of the open reading frame (Fig.…”
Section: Resultsmentioning
confidence: 94%
“…Boucher et al found that AlgU and RpoN have overlapping binding sequences at P algD , and that overexpression of rpoN inhibited mucoidy in PAO578 (20). However, the muc23 mutation was later characterized to be pilA 108 , which produces a truncated type IV pilin with an FTF tail at the C terminus of PilA108 to activate AlgW, which initiates the proteolytic cascade to degrade the full length of MucA (39). Similarly, Yin et al reported that overexpression of rpoN using pHERD20T resulted in the loss of mucoidy in PAO581 (37).…”
Section: Discussionmentioning
confidence: 99%
“…Large scale transposon mutagenesis was conducted on the wild type A. tertiaricarbonis RN12 strain by using the mariner transposon delivery vector pmini Himar RB1 as previously described [ 2 , 12 , 13 ]. A series of floc-formation-deficient mutants, whose liquid cultures were turbid and planktonic rather than flocculated as observed in the cultures of the wild type RN12 strain, had been isolated and the transposon insertion site was mapped in most of the floc-deficient mutants.…”
Section: Resultsmentioning
confidence: 99%